Relationship Characteristics and Contraceptive Use Among Dating and Cohabiting Young Adult Couples. Issue 1 (12th January 2015) - Wildsmith, Elizabeth; Manlove, Jennifer; Steward‐Streng, Nicole
Abstract : CONTEXT: Contraceptive decision making occurs in the context of relationships. Although many individual‐level characteristics have been linked to youths' contraceptive use, less is known about associations between contraceptive use and relationship‐level characteristics. METHODS: Data from the 2001–2002 romantic pair subsample of the National Longitudinal Study of Adolescent Health were used to describe characteristics of 322 dating relationships and 406 cohabiting relationships among young adults aged at least 18 years. Logistic regression was employed to assess associations between these characteristics and hormonal or long‐acting contraceptive use and condom use. Data from both partners allowed discordance in reports between partners in some measures to be examined. RESULTS: Cohabiting couples were less likely than dating couples to have used condoms (19% vs. 37%) and hormonal or long‐acting methods (40% vs. 57%) at last sex. In dating relationships, couples reporting discordant levels of intimacy and couples in which neither partner reported a high level of intimacy had greater odds of condom use than couples in which both partners reported high intimacy (odds ratios, 4.5 and 3.3, respectively); mistrust and male problem drinking were negatively associated with condom use (0.3 for each). For cohabiting couples, frequency of sex was negatively associated with condom use and hormonal method use (0.8 for each). CONCLUSIONS: At least for dating couples, contraceptive use is linked to multiple dimensions of relationships, particularly measures reflecting relationship quality—both positive and negative.